Exploiting New Systems-Based Strategies to Elucidate Plant–Bacterial Interactions in the Rhizosphere - Barret, M.; Tan, H.; Egan, F.; Morrissey, J.; Reen, F.; O'Gara, Fergal (John Wiley & Sons, 2013)
The rhizosphere is a site of intense interactions between plant and microorganisms. Molecular signaling between partners underpins the development of both the beneficial and pathogenic interactions that occur between plants and bacteria in nature. Despite the general acceptance that plant root exudates can influence the behavior and structure of bacterial communities in the rhizosphere, very little is known about the molecular mechanisms involved in this phenomenon. Analysis of the rhizospheric communities incorporating both established techniques, and recently developed “omic technologies,” can now facilitate investigations into the molecular basis underpinning the establishment of plant–microbial interactomes in the rhizosphere. These different molecular-based strategies employed to elucidate the complex interactions that occur between plant and bacterial communities in the rhizosphere are summarized in this chapter.